2019
DOI: 10.4014/jmb.1909.09007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Lactobacillus plantarum subsp. plantarum Producing C30 Carotenoid 4,4��-Diaponeurosporene and the Assessment of Its Antioxidant Activity

Abstract: Carotenoids are natural pigments widespread in plants, some animals, fungi, and photosynthetic or nonphotosynthetic bacteria [1]. Their antioxidant activities have also been extensively studied [2]. Carotenoids have interesting biological functions including antioxidant, anticancer, and anti-obesity effects and are widely used in foods, nutraceuticals, and the feed industry [3]. Structurally, carotenoids can be divided into carotenes (e.g., α-/βcarotene and lycopene) and xanthophylls (e.g., lutein, zeaxanthin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…H 2 O 2 , however, resulted in a significantly larger zone of inhibition for ∆crtN and to a lesser extent ∆crtP mutant strains (Figure 4d), which is consistent with an antioxidant role for carotenoids against oxidative damage from reactive oxygen species in the membrane (Kim et al, 2019;Kumar et al, 2019). In contrast, both hopanoiddeficient strains ∆shc and ∆hpnE exhibited higher sensitivity to all antibiotics tested.…”
Section: Isoprenoid-deficient Mutant Strains Are More Sensitive To Physicochemical Stressessupporting
confidence: 69%
“…H 2 O 2 , however, resulted in a significantly larger zone of inhibition for ∆crtN and to a lesser extent ∆crtP mutant strains (Figure 4d), which is consistent with an antioxidant role for carotenoids against oxidative damage from reactive oxygen species in the membrane (Kim et al, 2019;Kumar et al, 2019). In contrast, both hopanoiddeficient strains ∆shc and ∆hpnE exhibited higher sensitivity to all antibiotics tested.…”
Section: Isoprenoid-deficient Mutant Strains Are More Sensitive To Physicochemical Stressessupporting
confidence: 69%
“…Lactobacillus pentosus KCCP11226 harbors C 30 carotenoid biosynthetic genes ( crtM and crtN ), shows high carotenoid production and survival under oxidative stress, and is considered a functional probiotic. 141 Notably, aerobic growth conditions, while slowing down growth, significantly induced carotenoid production in Enterococcus gilvus, 142 which indicated that aerobic culture conditions may contribute to conferring oxidative stress tolerance in carotenoid-producing LAB. Further research revealed that aerobic growth conditions not only affected crtN and crtM expression, but also the biosynthesis of the carotenoid precursor isoprenoid via mevalonate in E. gilvus .…”
Section: Antioxidant Properties Of Probiotic Labmentioning
confidence: 98%
“…This strain demonstrated the highest survival when exposed to OS, and the highest ability to scavenge DPPH free radicals. Carotenoid production in the strain was increased following exposure to 7 mM H 2 O 2 [150].…”
Section: Other Probiotic Metabolites and Cellular Components With Antioxidant Propertiesmentioning
confidence: 99%